Hybrid AgNPs/MEH-PPV nanocomplexes with enhanced optical absorption and photoluminescence properties. (2nd November 2018) - Ali, Nasir; Bi, Gang; Khesro, Amir; Khan, Majid; Lang, Jiawei; Samreen, Ayesha; Wu, Huizhen
Abstract : Fluorescent semiconducting conjugated polymer nanoparticles (CPNs) are promising candidates for enhanced luminescent devices and bioimaging. Abstract : Fluorescent semiconducting conjugated polymer nanoparticles (CPNs) are promising candidates for enhanced luminescent devices and bioimaging. The key aspect of all fluorescent materials is their high radiative yield. Combination of CPNs with metal nanoparticles (MNPs) is one of the ways to increase their fluorescent yield. Most of such combinations are introduced in the forms of sophisticated core–shells and thin films or layers. Herein, we synthesized CPNs of poly[2-methoxy, 5-(2′-ethylhexyloxy)-1, 4-phenylenevinylene] (MEH-PPV) and silver nanoparticles (AgNPs) in aqueous solution in the form of metal–polymer nanocomplexes (MPNCs), which are not only easily achievable but also show significantly enhanced optical absorption and luminescence properties. To synthesize MPNCs, AgNPs with different molar ratios were added to a colloidal solution of CPNs. The adsorption of AgNPs on the surfaces of the CPNs was confirmed by transmission electron microscopy and UV-VIS absorption spectroscopy. Fluorescence and optical absorption spectroscopies revealed a substantial increase in the optical absorption and photoluminescence (PL) intensity of the MPNCs. It was observed that at optimum concentrations of AgNPs and CPNs in the colloidal solution of MPNCs, the PL intensity is enhanced by ∼11 fold. The increase in PL intensity is attributed to the energy transfer from AgNPs to CPNs via near-field-coupling and electric field enhancement in the nanogaps present among the adsorbed AgNPs on the surfaces of the MPNCs, which is confirmed by finite difference time domain (FDTD) simulations. Since the MPNCs as well as their ingredients were prepared in aqueous solutions, we believe that such nanocomplexes could find use not only in enhanced fluorescent devices but also in therapeutics and diagnostics.